Estudio de prefactibilidad para la instalación de una planta productora de macerados en base a aguardiente de caña de azúcar (Saccharum officinarum) en la región Amazonas - Barbadillo Balarezo, Bruno (2020)
The main project target is to establish the viability in terms of technological, economic, financial, social and market terms for the installation of a processing plant of macerated liquor based on sugarcane (Saccharum officinarum) schnapps located in Amazonas. Through a survey we have been able to establish the intensity and purchase intention of potential customers. We have considered the entire population located in Peru, which was segmented by the socioeconomic levels A, B and C. Also, considering people between 20 and 64 years old. Within these conditions applied in our market study, we determined our project demand in 53,423 bottles of 750 ml by the year 2025. In terms of location, we carried out a study focused in Amazonas. Finally, the city of Chachapoyas was considered, as it stood out in a greater number of factors such as the availability of energy and water, urban development and proximity to raw materials. Once the demand for the project has been determined, the size of the plant is established. The market was the factor that determined the size of the plant with a capacity of 53,424 bottles of finished product, also considering that the project must produce at least 26,442 units approximately to be profitable. Through economic and financial analysis, the optimal form of financing was determined. In addition, the financial indicators for the project were calculated in which an IRR was obtained with a value of 51.47% and a VNA of S/. 680,222 for the 5-year project. The indicators are complemented with an analysis of price and demand variation to determine the viability of the project in different scenarios. Likewise, the investment recovery period is 2.39 years with a benefit/cost ratio of 2.63 PEN for each 1 PEN invested. Finally, it can be ascertained as feasible the viability in terms of technological, economic, financial, social and market terms for the installation of a processing plant of macerated liquor based on sugarcane (Saccharum officinarum) schnapps located in Amazonas.